Penegakan Hukum terhadap Guest House dan Villa tanpa Izin di Kabupaten Badung - Cinta Saraswati; I Made Arjaya; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2020)
Tourism is a source of local revenue and its investment is a potentially vital production factor in the service production business in this field. To support tourism accommodation in the tourist area of ​​Badung Regency, guest houses (boarding houses/rented houses) and villas are needed as support. Especially in Badung Regency, in the Canggu area, many houses are used as guest houses for guests who want to stay in Bali. This study aims to determine the supervision of Guest Houses and Villas in Badung Regency, and to determine the application of sanctions against guest houses and villas that violate permits in Badung Regency. The method in this research is a type of normative legal research which is carried out with the method of recording and reviewing based on legal materials. In this study, studying and gathering information through legal science books without deviating from positive law in order to form a conclusion. The research results show that the supervision of Guest Houses and Villas in Badung Regency is given the authority by the Regional Regulation through the Civil Service Police Unit which is assigned to monitor every building that does not have a permit in the Badung Regency area, especially in the Canggu area. Then, sanctions against violators are in the form of warnings 3 times, if they do not disobey the villa owner, they will be subject to forced demolition by officers.